PERFORMANCE OF SORGHUM HYBRIDS UNDER DIFFERENT NITROGEN LEVELS IN RICE-FALLOW CONDITIONS OF NORTH COASTAL ANDHRA PRADESH - B. SRI SAI SIDDARTHA NAIK (The Journal of Research ANGRAU, 2018)
The field experiment was conducted on sandy loam soil during Rabi 2016-17. The treatments comprised combination of four sorghum hybrids and four nitrogen levels laid out in split plot design with three replications. Among the hybrids, CSH 25 was recorded with highest yield (6841 kg ha-1) and panicle length (28.25 cm).With the different nitrogen levels tested, application of 120 kg N ha-1(7491 kg ha-1)was recorded with highest yield, panicle length (29.90 cm) and test weight (3.97). However, stover yield was highest with hybrid CSH 15R and with 120 kg N ha-1. Gross returns, net return and B:C ratio were also highest with CSH 25 and with highest N level (120 kg ha-1). Hence, the study revealed that for rice fallow situation sorghum can be successfully grown with hybrid CSH-25 and application of 120 kg N ha-1which were found promising for North Coastal Zone of Andhra Pradesh.